Лабораторні та ехокардіографічні зміни при хронічній серцевій недостатності у жінок з надлишковою масою тіла та ожирінням залежно від функціонального класу захворювання - Бідзіля, Петро Петрович (My University, 2015)
Досліджено лабораторні та ехокардіографічні зміни при хронічній серцевій недостатності (ХСН) у жінок з надлишковою масою тіла та ожирінням. Зі збільшенням функціонального класу ХСН відбуваються характерні зміни лабораторних показників, поглиблення дилатації серця, концентричного типу гіпертрофії міокарда, кальцинування та регургітації клапанів. Поширюється систолічна, діастолічна дисфункція міокарда та їх поєднання, розвивається легенева гіпертензія. The half of all patients with CHF is women most of them has a preserved ejection fraction (EF) of the left ventricle (LV) and near 35 % of their death from cardiovascular pathology are caused by CHF. The aim of research was the study of changes of laboratory and echocardiographic parameters at CHF in women with overweight and obesity depending on the functional class (FC) of disease. Methods: There were examined 203 women with CHF of 1–111 FC with overweight and abdominal obesity of 1–111 degree. All patients underwent laboratory and echocardiographic examination. Processing of received results was carried out using parametric and nonparametric statistics depending on size and distribution of parameters. Results: At CHF progress the level of hemoglobin, erythrocytes, lymphocytes, prothrombin, albumin in blood and the speed of glomerular filtration decrease. The content of segmented neutrophils, creatinine and urea, speed of erythrocytes sedimentation increases. The structural changes of myocardium and valvate apparatus are presented as the more significant dilatation of heart cameras, progress of LV hypertrophy, calcination and regurgitation of valves. At CHF progress the changes of myocardium functional state are characterized with formation of systolic and diastolic LV dysfunction of the 1 type and with the spread of its combination and progress of pulmonary hypertension. In most examined patients the remodeling of myocardium is presented as concentric LV hypertrophy which frequency decreases with growth of CHF FC at the expense of the spread of eccentric hypertrophy. The percent of concentric remodeling of LV decreases with CHF intensification. Conclusions: With an increase of CHF FC in women with overweight and obesity take place the typical laboratory changes in blood, the structural reconstruction of the heart and disorder of myocardium functional state.
Keywords: лабораторні зміни; ехокардіографія; хронічна серцева недостатність; функціональний клас; жінки; ожиріння; laboratory changes; echocardiography; chronic heart failure; functional class; women; obesity